High thermal response rate and super low supercooling degree microencapsulated phase change materials (MEPCM) developed by optimizing shell with various nanoparticles. (September 2019) - Zou, Deqiu; Liu, Xiaoshi; He, Ruijun; Huang, Li
Graphical abstract: Highlights: MEPCM with graphene, CNT and nano-Ag doped into shell were prepared respectively. Morphology and thermal response rate of MEPCM were compared. MEPCM doped with 0.02% graphene exhibits the highest thermal response rate. Supercooling degree of MEPCM can be reduced to 0.5 °C. Abstract: Low thermal conductivity and high supercooling degree are the two major drawbacks for microencapsulated phase change materials (MEPCM). To improve thermal performance, MEPCM have been prepared and characterized using paraffin as the core and various nanoparticles (graphene, CNT and nano-Ag) doped into melamine urea-formaldehyde as the shell. Surface morphology and thermal response rate were compared. The results showed that MEPCM with graphene and nono-Ag doped into shell had good morphology. Further comparison indicated that MEPCM with shell doped with 0.02% graphene exhibited the quickest thermal response rate. Based on that, MEPCM with various core/shell ratios have been prepared and DSC test was conducted. Results showed that supercooling degree reduces with the decrease of core/shell ratio and the value can be reduced to 0.5 °C at the core/shell ratio of 1/2, which is the lowest value in publications for MEPCM. The present study can provide significant guidance for nanoparticles selection and core/shell ratio determination for preparation of MEPCM with high thermal response rate and super low supercooling degree.